Herpes simplex keratitis: challenges in diagnosis and clinical management - Azher TN (Dove Medical Press, 2017)
Tayaba N Azher,1 Xiao-Tang Yin,1 Deena Tajfirouz,1 Andrew JH Huang,2 Patrick M Stuart1 1Department of Ophthalmology, Saint Louis University, 2Department of Ophthalmology and Visual Sciences, Washington University, St Louis, MO, USA Abstract: Herpes simplex virus is responsible for numerous ocular diseases, the most common of which is herpetic stromal keratitis. This is a recurrent infection of the cornea that typically begins with a subclinical infection of the cornea that establishes a latent infection of sensory ganglia, most often the trigeminal ganglia. Recurring infections occur when the virus is reactivated from latency and travels back to the cornea, where it restimulates an inflammatory response. This inflammatory response can lead to decreased corneal sensation, scarring, and blindness. The diagnosis of these lesions as the result of a recurrent herpes simplex virus infection can at times be problematic. Currently, herpetic stromal keratitis is diagnosed by its clinical presentation on the slit-lamp examination, but the literature does not always support the accuracy of these clinical findings. Other diagnostic tests such as polymerase chain reaction assay, enzyme-linked immunosorbent assay, immunofluorescent antibody, and viral cultures have provided more definitive diagnosis, but also have some limitations. That said, accurate diagnosis is necessary for proper treatment, in order to prevent serious consequences. Current treatment reduces the severity of lesions and controls further viral spread, but does not provide a cure. Keywords: herpes simplex virus, herpetic stromal keratitis, cornea